Уведення в асептичну культуру рідкісної ендемічної рослини Atocion lithuanicum (Zapal.) Tzvel. - Мартинюк, В.О.; Голубенко, А.В.; Гуменюк, Г.Б. (Фактори експериментальної еволюції організмів, 2014)
Aims. Introduction of the rare endemic species Atocion lithuanicum (Zapal.) Tzvel. to in vitro culture for its preservation ex situ. Research of the seed germination, in vitro vegetation, microclonal reproduction features and morphogenetic potential of A. lithuanicum plants. Methods. A. lithuanicum seeds were germinated in vitro using our own modification of the traditional methods. Explants of aseptic seedlings were cultivated on a ½ Murashige & Skoog basal medium with different hormonal composition. Results. It was discovered that A. lithuanicum seeds germinate in the light at 24°С. It was found that adding low concentrations of kinetine and indole acetic acid to the medium stimulates the microclone formation. Conclusions. The A. lithuanicum seeds have no dormancy state. The A. lithuanicum plants show a high ability for morphogenesis in vitro. The reproduction of A. lithuanicum in the aseptic culture is one of the possible ways to preserve this rare endemic species.

Key words: Atocion lithuanicum (Zapal.) Tzvel., seed germination, in vitro culture, clonal micropropagation.